PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PEMBELAJARAN GENERATIF DENGAN GUIDED TEACHING TECHNIC UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA KELAS X SMA PADA MATERI MOMENTUM DAN IMPULS - Fhia Indriani Saputri; Muhammad Nasir; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to development a generative learning model with Guided Teaching Technic in Momentum and Impulse for X class of Senior High School which is feasible to measure students physics problem solving abilities. The type of research used in this research is Research and Development (R&D) research using the ADDIE development model which stands for Analysis, Design, Development, Implementation, and Evaluation. In this study, the validation stage was carried out by 3 experienced Physics Education lecturers. The research instrument was a questionnaire in the form of a checklist. This study uses two types of data collected, namely quantitative data obtained from the score of the validator's assessment and student's assessment, while the qualitative data is in the form of criticism and suggestions from the validator of the product being developed and a description of the implementation of the product trial. Data analysis in this study used descriptive analysis by calculating the index of each indicator used to determine the validity of the learning tools developed. The results of this study provide information that the Generative learning model with Guided Teaching Technic developed in Momentum and Impulse is valid with the development of Learning Implementation Plan (RPP) in the high category, the development of Student Worksheets (LKPD) is very high category, and the development of the Knowledge Test Instrument category is very high and can be used in learning to support the teaching and learning process so that it becomes better.Keywords: Development, Generative, Guided Teachung Technic, Momentum and Impulse